A technical note on the uncertainties of the Chen correlation for the boiling heat transfer coefficient at saturated flow - Poulopoulou, Electra; Petropoulos, Nick (Nuclear technology & radiation protection, 2024)
The so-called Chen correlation for the boiling heat transfer coefficient at saturated flow has been, since 1966, the year of its publication, largely cited as one of the most successful of its kind. As well known, it is based on adding terms respective to heat transfer in the liquid part and heat transfer in the steam part. The respective formulae incorporate both the Reynolds number factor F and the suppression factor S. At the time, Chen accepted F and S to be derived graphically. Nevertheless, and mainly for computational purposes, several equations have been proposed approximating these two factors. These equations have been reviewed for accuracy and typos and are now widely accepted. However, there has not been any attempt to associate the results of the Chen correlation with the expected uncertainty. The objective of this short report is to process the Chen correlation in terms of its uncertainty based on the uncertainty of factors F and S. The uncertainties of F and S were derived digitally from the graphs of F and S in the original work of Chen of 1966. Following digitization the uncertainty data were processed to provide uncertainty formulae in polynomial form. It was accepted that the uncertainty level of F and S was k =1.